Proposed Construction for Oxygen Indicator Model C (1944)
The device depicted is likely one of the models constructed for the National Defense Research Committee. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Beckman Instruments, Inc.